2014
DOI: 10.1007/s10464-014-9646-2
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Community Intervention for the Prevention of Suicide and Alcohol Abuse with Yup'ik Alaska Native Youth: The Elluam Tungiinun and Yupiucimta Asvairtuumallerkaa Studies

Abstract: The Elluam Tungiinun and Yupiucimta Asvairtuumallerkaa studies evaluated the feasibility of a community intervention to prevent suicide and alcohol abuse among rural Yup’ik Alaska Native youth in two remote communities. The intervention originated in an Indigenous model of protection, and its development used a community based participatory research (CBPR) process. Feasibility assessment aimed to assess the extent to which (1) the intervention could be implemented in rural Alaska Native communities, and (2) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…The individual, family, and community protective factors predictor variables of RFL and RP function as intermediate prevention strategy target variables in the culturally grounded theoretical model guiding the Qungasvik multilevel intervention. Research has produced promising preliminary findings of growth in dose related youth RFL and RP outcomes and in parent and community level protective outcomes in response to exposure to Qungasvik as a preventative intervention (Allen, Mohatt, Fok, & Henry, 2009; Mohatt, Fok, Henry, & Allen, 2014). …”
Section: A Protective Factors Model For Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual, family, and community protective factors predictor variables of RFL and RP function as intermediate prevention strategy target variables in the culturally grounded theoretical model guiding the Qungasvik multilevel intervention. Research has produced promising preliminary findings of growth in dose related youth RFL and RP outcomes and in parent and community level protective outcomes in response to exposure to Qungasvik as a preventative intervention (Allen, Mohatt, Fok, & Henry, 2009; Mohatt, Fok, Henry, & Allen, 2014). …”
Section: A Protective Factors Model For Preventionmentioning
confidence: 99%
“…Previous research has identified intervention dose related growth in measures of these intermediate intervention target protective factors hypothesized in the theory of change to be responsible for the Qungasvik intervention effects (Mohatt et al, 2014). However, despite our observations, in conducting the intervention, regarding its impacts on community and family functioning and their network structures, we understand little regarding the relationship of the social networks within these geographically remote, tight knit, kinship based Yup’ik rural communities to these protective factors variables.…”
Section: A Protective Factors Model For Preventionmentioning
confidence: 99%
“…It is important to note that there were important differences between the organizational structures and the resources of the grant funding across the intervention communities; however, though many of the details and events differed in important ways, the process was similar. As described in greater detail in Mohatt et al (2014), some of these differences, such as the shorter time frame and lesser monetary resources of the grant mechanism funding for the project in the second community, provide part of the explanation for the observed differences in outcomes.…”
Section: Entry Into a Cbpr Intervention Development Process In Southwmentioning
confidence: 99%
“…These items were dropped from the final scale. The final version of the scale has been used in prevention studies in communities with samples of less than 60 (Mohatt, Fok, Henry, Allen, & People Awakening Team, 2014). Removal of redundant and poorly functioning items results in a briefer measure that discriminates participants, improve measurement precision and ultimately increase power in detecting change.…”
Section: Strategies For Increasing Sensitivity Of Measures To Changementioning
confidence: 99%